Agreeableness modulates mental state decoding: Electrophysiological evidence - Pisanu, Elisabetta; Arbula, Sandra; Rumiati, Raffaella Ida (Human brain mapping, 2024)
Agreeableness is one of the five personality traits which is associated with theory of mind (ToM) abilities. One of the critical processes involved in ToM is the decoding of emotional cues. In the present study, we investigated whether this process is modulated by agreeableness using electroencephalography (EEG) while taking into account task complexity and sex differences that are expected to moderate the relationship between emotional decoding and agreeableness. This approach allowed us to identify at which stage of the neural processing agreeableness kicks in, in order to distinguish the impact on early, perceptual processes from slower, inferential processing. Two tasks were employed and submitted to 62 participants during EEG recording: the reading the mind in the eyes (RME) task, requiring the decoding of complex mental states from eye expressions, and the biological (e)motion task, involving the perception of basic emotional actions through point‐light body stimuli. Event‐related potential (ERP) results showed a significant correlation between agreeableness and the contrast for emotional and non‐emotional trials in a late time window only during the RME task. Specifically, higher levels of agreeableness were associated with a deeper neural processing of emotional versus non‐emotional trials within the whole and male samples. In contrast, the modulation in females was negligible. The source analysis highlighted that this ERP‐agreeableness association engages the ventromedial prefrontal cortex. Our findings expand previous research on personality and social processing and confirm that sex modulates this relationship. Agreeableness personality trait affects brain's activity during mental state decoding, namely during the first stage of theory of mind. Subjects with high agreeableness show a deeper neural processing of emotional versus non‐emotional trials in a late time window and by mainly engaging the ventromedial prefrontal cortex.